Nawyki żywieniowe i aktywność fizyczna młodzieży szkół ponadgimnazjalnych jako czynniki ryzyka wystąpienia otyłości = School students’ dietary habits and physical activity as a risk factor of the obesity - Kocka, Katarzyna; Bartoszek, Agnieszka; Fus, Małgorzata; Rząca, Marcin; Łuczyk, Marta; Bartoszek, Adrian; Muzyczka, Katarzyna; Nowicki, Grzegorz; Ślusarska, Barbara (Journal of Education, Health and Sport, 2016)
Kocka Katarzyna, Bartoszek Agnieszka, Fus Małgorzata, Rząca Marcin, Łuczyk Marta, Bartoszek Adrian, Muzyczka Katarzyna, Nowicki Grzegorz, Ślusarska Barbara. Nawyki żywieniowe i aktywność fizyczna młodzieży szkół ponadgimnazjalnych jako czynniki ryzyka wystąpienia otyłości = School students’ dietary habits and physical activity as a risk factor of the obesity. Journal of Education, Health and Sport. 2016;6(7):439-452. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.58452 http://ojs.ukw.edu.pl/index.php/johs/article/view/3708 The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 15.06.2016. Revised 09.07.2016. Accepted: 21.07.2016. Nawyki żywieniowe i aktywność fizyczna młodzieży szkół ponadgimnazjalnych jako czynniki ryzyka wystąpienia otyłości School students’ dietary habits and physical activity as a risk factor of the obesity Katarzyna Kocka1, Agnieszka Bartoszek1, Małgorzata Fus2, Marcin Rząca3, Marta Łuczyk3, Adrian Bartoszek4, Katarzyna Muzyczka1, Grzegorz Nowicki1, Barbara Ślusarska1 1Zakład Medycyny Rodzinnej i Pielęgniarstwa Środowiskowego, Katedra Onkologii i Środowiskowej Opieki Zdrowotnej, Wydział Nauk o Zdrowiu, Uniwersytet Medyczny w Lublinie 2Absolwentka Wydziału Pielęgniarstwa i Nauk o Zdrowiu Uniwersytetu Medycznego w Lublinie 3Zakład Onkologii, Katedra Onkologii i Środowiskowej Opieki Zdrowotnej, Wydział Nauk o Zdrowiu, Uniwersytet Medyczny w Lublinie 4Student Wydziału Lekarskiego, Uniwersytet Medyczny w Łodzi Słowa kluczowe: nawyki żywieniowe, aktywność fizyczna, otyłość, młodzież. Key words: dietary habits, physical activity, obesity, school students. Streszczenie Wstęp Według raportu na świecie 155 milionów dzieci w wieku szkolnym ma nadmierną masę ciała. Szacuje się, że co piąta osoba populacji rozwojowej w Europie ma nadwagę lub otyłość. Podobnie w Polsce obserwuje się tendencję wzrostową częstości występowania nadmiernej masy ciała u dzieci i młodzieży. Cel Celem badań była analiza nawyków żywieniowych i aktywności fizycznej młodzieży jako czynników ryzyka otyłości. Materiał i metoda Badania przeprowadzono w 2014 roku wśród młodzieży lubelskich szkół średnich. Badaniami objęto 150 osób w wieku 16 - 19 lat. Zastosowaną metodą badawczą był sondaż diagnostyczny. Do zebrania danych, jako narzędzie badawcze wykorzystano autorski kwestionariusz ankiety składający się z 29 pytań. Zgromadzone wyniki badań poddano analizie statystycznej z wykorzystaniem testu Chi2. Wyniki badań Analizując nawyki żywieniowe badanej młodzieży można stwierdzić, że 40,00% badanych nie spożywa regularnie posiłków. Ponad połowa ankietowanych (53,33%) spożywa przekąski pomiędzy głównymi posiłkami, jedynie 10,00% osób zadeklarowało, że nie spożywa produktów typu fast-food. Interpretacja wyników badań własnych dotyczących aktywności fizycznej młodzieży wykazała że, niemal 2/3 ankietowanych (64,67%) odpowiedziało, że czas wolny spędza w bierny sposób oglądając telewizję bądź korzystając z komputera. Wnioski Wśród nawyków żywieniowych sprzyjających otyłości u badanej młodzieży stwierdzono: nieregularne spożywanie posiłków, niedostateczną ilość owoców i warzyw w codziennym jadłospisie oraz spożywanie przekąsek pomiędzy głównymi posiłkami –głównie słodyczy. Stopień aktywności fizycznej badanej grupy jest niezadowalający. Młodzież chętniej wybiera bierne formy spędzania czasu wolnego. Abstract Introduction According to the report of the International Obesity Task Force (IOTF) there are 155 milion school students with overweight and obesity in Europe. The same trend towards an increase in it have also been observed in Poland. Aim The aim of this study was to analyse school students` dietary habits and physical activity as a risk factor of the obesity. Material and methods The studies were conducted on the representative, random sample of 150 school students from Lublin secondary school aged 16-19 years in 2014. The date was assessed using a survey questionnaire consist of 29 questions created by the authors. The evaluation of the date was calculated using the a chi-squared test. Results The studies showed that 40% of the school students consumed the meals irregularly. More than half of the school students consumed bad snacks among meals while only 10% did not. The results showed that two thirds of the school students (64.67%) spent their time for leisure in front of the TV or computer. Conclusions The results indicates that dietary habits such as irregularly frequency of the eating, not many fruit and vegetables in the diet as well eating snacks between meals, mainly sweets could increase a risk of obesity Low level of the physical activity among school students was observed. Teenagers are more likely to spend their leisure time inactively.